The Benefits of Access: Evidence from Private Meetings with Portfolio Firms - BECHT, MARCO; FRANKS, JULIAN; WAGNER, HANNES F. (Journal of Finance, 2026)
ABSTRACT We use large language models to analyze the content of 4,700 private meetings between a large active asset manager and its portfolio firms. The high‐level meetings convey mostly soft information about the firm, and little about industry or market. Fund manager meetings focus on business models and financial metrics, while governance specialist meetings focus on environmental, social, and governance risks; 0.4% of meetings discuss material nonpublic information. Trades by fund managers increase with meetings attended by senior management, rated as unusually good or bad, where the tone is significantly positive or negative, or assessed as creating consensus. Meeting‐informed portfolios can generate significant outperformance.